Penggunaan Media Pembelajaran Pop-Up Book Dalam Keterampilan Berbicara Bahasa Jerman - Fatimah Fatimah; Wahyu Kurniati Asri; Nurming Saleh (Phonologie : Journal of Language and Literature, 2021)
Abstract. This study aims to determine the planning, process, and results of pop-up book learning media in the German speaking skills of class XI students of SMA Negeri 8 Makassar. This research is a classroom action research which consists of two cycles. The subjects of this study were students of class XI MIPA SMA Negeri 8 Makassar, totaling 30 students. This research data consists of two types, namely qualitative data and quantitative data. Qualitative data was obtained through observation while quantitative data was obtained through speaking skills tests in cycle 1 and cycle II. The results showed that the students' speaking skills in the first cycle were 77.91 and in the 85.62 cycle. These results indicate that the use of pop-up book learning media improves the German speaking skills of students in class XI MIPA SMA Negeri 8 Makassar.